NASCAR : leading a marketing transformation in a time of crisis - Anderson, Eric T., (SAGE knowledge. Cases., 2016)
It is February 2011 and Brian France, CEO of NASCAR (the National Association for Stock Car Auto Racing), is facing a crisis. In the last five years, attendance at weekend NASCAR races has fallen 22 percent and television viewership has declined 30 percent. Key marketing sponsors have recently left the sport. At the same time, the US economy was only beginning to recover from an economic recession that had an adverse impact on the sport of auto racing as a whole. Some leaders within NASCAR counseled Brian that these trends in attendance, viewership, and sponsorship stemmed from the recession and that NASCAR should continue with business as usual. But Brian sensed that the industry needed fundamental change. This case study discusses this topic.